A multicentre, double blind, randomised, placebo controlled trial of anakinra (Kineret), a recombinant interleukin 1 receptor antagonist, in patients with rheumatoid arthritis treated with background methotrexate. Issue 9 (13th April 2004) - Cohen, S B; Moreland, L W; Cush, J J; Greenwald, M W; Block, S; Shergy, W J; Hanrahan, P S; Kraishi, M M; Patel, A; Sun, G; Bear, M B
Abstract : Objective: To assess the efficacy and safety of 100 mg daily anakinra (Kineret), a recombinant form of the naturally occurring interleukin 1 receptor antagonist, plus methotrexate (MTX) in reducing the signs and symptoms of rheumatoid arthritis (RA). Methods: Patients with active RA (n = 506) despite current treatment with MTX were enrolled in this multicentre, double blind, randomised, placebo controlled study. Patients received subcutaneous injections of anakinra 100 mg/day or placebo. They were assessed monthly for 6 months for improvement in signs and symptoms of RA and for adverse events. The primary efficacy measure was the percentage of patients attaining ACR20 response at week 24. Results: Significantly greater proportions of patients treated with anakinra compared with placebo achieved ACR20 (38% v 22%; p<0.001), ACR50 (17% v 8%; p<0.01), and ACR70 (6% v 2%; p<0.05) responses. The response to anakinra was rapid; the proportion of patients with an ACR20 response at the first study assessment (4 weeks) was twice as high with anakinra as with placebo (p<0.005). Clinically meaningful and statistically significant responses were also seen in individual components of the ACR response (for example, Health Assessment Questionnaire, pain, C reactive protein levels, and erythrocyte sedimentation rate). Anakinra was well tolerated, with a safety profile, similar to that of placebo with one exception: mild to moderate injection site reactions were more common with anakinra than with placebo (65% v 24%). Conclusions: This study confirms previous observations from a dose-ranging study showing that anakinra, in combination with MTX, is an effective and safe treatment for patients with RA who have inadequate responses to MTX alone.